Effects on Dimensional Accuracy of Microstereolithographically Machined Parts after Addition of Light Absorber (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The paper’s aim is to investigate the influence ofadded light absorber (Tinuvin® 327) on dimension accuracyof three-dimensional (3D) micro-parts manufactured by adynamic mask projection microstereolithography (µSL)system. One of the common problems withstereolithography systems, and particularly with µSL is theuncontrolled cure depth of the UV light when fabricatingdown-facing surfaces. To overcome this problem, lightabsorber is commonly used to control the cure depth. Yetthe influence of light absorber on the dimension accuracy ofmanufactured parts is not fully understood and needs to beinvestigated. This work explores the effect on part accuracyof adding four different concentrations of Tinuvin®327 toPIC-100 acrylate resin without light absorber. A benchmark part has been designed to evaluate the effect of theadded Tinuvin®327 on linear, position, and geometric dimensions. Results show that Tinuvin®327 has significanteffects on part accuracy.